Feasibility of Replacing Chemical Fertilizer by Using Organic Fertilizer in Wheat (Triticum aestivum) Considering Yield Contributing Characters and Yield - Akhter, Z; Imam, MH; Razzak, MA; Akhter, AHMMR; Akhter, M (Journal of Environmental Science and Natural Resources, 2015)
The experiment comprised of 10 treatments, such as T0: Control condition; T1: All chemical fertilizer as recommended dose; T2: Cowdung as recommended dose; T3: Compost as recommended dose; T4: ½ Cowdung + ½ Compost; T5: Cowdung + Compost; T6: Cowdung + ½ Chemical fertilizer; T7: Compost + ½ Chemical fertilizer; T8: Cowdung + Compost +½ Chemical fertilizer and T9: ½ Cowdung + ½ Compost + ½ Chemical fertilizer. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Data on different growth characters and yield were recorded. Among the treatments all chemical fertilizers as recommended dose (T1) and cowdung + compost + ½ chemical fertilizer (T8) were found superior considering all yield contributing characters and yield. At 30 (Days after Sowing) DAS, the longest plant was recorded from T8 (27.93 cm), while the shortest plant was found in T0 (23.13 cm). At 50, 70, 90 DAS and harvest the longest plant was recorded from T1 (52.13 cm, 82.13 cm, 85.93 cm and 95.21 cm), whereas the shortest plant was obtained from T0 (41.14 cm, 65.84 cm, 70.77 cm and 76.00 cm). At 30, 50, 70, 90 DAS and harvest the maximum number of tillers hill-1 was recorded from T1 (2.00, 5.64, 6.93, 6.15 and 5.78), whereas the minimum number was found in T0 (1.33, 2.87, 4.20, 3.94 and 3.72). The longest spike (19.86 cm), maximum number of spikelets spikes-1 (20.33), maximum number of filled grains spike-1 (34.00), highest grain yield (3.71 t ha-1) and highest straw yield (5.78 t ha-1) was attained from T1 and the shortest spike (14.33 cm), minimum number of spikelets spikes-1 (14.18), minimum number of filled grains spike-1 (21.53), lowest grain yield (2.06 t ha-1) and lowest straw yield (4.49 t ha-1) was recorded from T0. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22066 J. Environ. Sci. & Natural Resources, 6(1): 203-208 2013